(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents ways to use SMART educational technologies to improve national virtual tourism in English language classes through professional skills, to make the educational process more interactive, intuitive and individualized, to improve virtual tourism through SMART technologies interactive content (i.e. interactive lessons related to virtual tourist attractions), materials, 3D models and video tours, and to strengthen students’ knowledge through teaching English through virtual tourism.